Memorandum of understanding between Universiti Teknologi MARA and Herbert Smith Freehills LLP / Fakulti Undang-Undang - Universiti Teknologi MARA, Fakulti Undang-Undang (Universiti Teknologi MARA (UiTM), 2019)
In line with the “UiTMLaw goes Global” aspiration, this collaboration is a leading part of the internationalization endeavour carried out by the UiTMLaw. Herbert Smith Freehills has already provided, and will continue to provide, several guest lectures, covering both technical legal issues and soft skills, at the faculty in 2018 and 2019. Additionally, Herbert Smith Freehills has entered into an informal arrangement to offer at least one internship position to students from the faculty as part of the firm’s annual internship programme.